99 percenters: An examination of the misconduct careers of the most violent and disruptive incarcerated delinquents. (September 2021) - Butler, H. Daniel; Caudill, Jonathan W.; Craig, Jessica M.; DeLisi, Matt; Trulson, Chad R.
Abstract: The function of correctional institutions is to maintain institutional security and safety, and institutional misconduct undermines that security. Few studies have examined the individuals who pose the greatest threat to institutional security and are responsible for the greatest number of misconduct incidents (i.e., the 99th percentile of misconducts). This study examines youthful offenders incarcerated in Texas state juvenile facilities who engage in the most frequent and most violent misconduct incidents through a series of logistic regression and ROC-AUC models. The findings indicate that younger age, African-American status, gang activity during confinement, being a danger to self, and involvement in multiple forms of treatment evince a higher risk of engaging in the 99th percentile of total and violent misconduct regardless of model specification. Other factors such as commitment offense, adverse childhood experiences, and sex have differential effects depending on whether the 90th or 99th percentile thresholds are considered. Youth in the 90th percentile account for 49% of total misconduct and 50% of violent misconduct. Youth in the 99th percentile account for 11% of total misconduct and 51% of violent misconduct. We discuss implications for policy and practice and the importance of understanding antisocial development of youthful offenders and their institutional maladjustment. Highlights: Younger age, African-American status, gang activity during confinement, being a danger to self, and involvement in multiple forms of treatment evince a higher risk of misconduct. Other factors such as commitment offense, adverse childhood experiences, and sex have differential effects. Youth in the 90th percentile account for 49% of total misconduct and 50% of violent misconduct. Youth in the 99th percentile account for 11% of total misconduct and 51% of violent misconduct. We discuss implications for policy and practice and the importance of youthful offenders and their institutional maladjustment.